PRIMA 2016 : princiles and practice of multi-agent systems : 19th International Conference, Phuket, Thailand, August 22-26, 2016, Proceedings /: princiles and practice of multi-agent systems : 19th International Conference, Phuket, Thailand, August 22-26, 2016, Proceedings. (2016) - Unknown
No abstract available